The influence of media slant on short sellers - Knill, April; Liu, Baixiao; McConnell, John J.; McKenzie, Glades (Journal of Corporate Finance, 2024)
Using the positive shift in tone of Fox News coverage of macroeconomic news after the Republican Bush election in 2000, we investigate whether media slant influences the investment decisions of short sellers. We find that firms headquartered in Republican-leaning townships with Fox News availability experienced a relative decrease in short interest post the 2000 election. We further find that the relative decrease is more pronounced for firms that are more subject to investors' home bias. We interpret our findings to mean that short sellers, as sophisticated as they may be, are not immune to the slant in media coverage.